The Color of Drinking Survey Questionnaire for Measuring the Secondhand Impacts of High-Risk Drinking in College Settings: Validation Study - Marconi, Agustina (2025)
Background:The “Color of Drinking” is a study conducted at the University of Wisconsin-Madison. It examines the secondhand harms of high-risk drinking on college students of color and explores the connection between alcohol use and the campus racial climate. Since its findings were released in 2018, this study has received significant attention from other college settings around the country.Objective:This study aims to describe the development of the most recent version of the Color of Drinking questionnaire and to assess its internal consistency, test-retest reliability, and construct validity in a sample of undergraduate students attending the University of Wisconsin-Madison.Methods:This is an observational, analytic study. Questionnaire design experts revised the original instrument, and in-depth cognitive interviews with students were conducted to evaluate comprehensibility and acceptability. The revised questionnaire was administered 2 times, 3 to 4 weeks apart, in a sample of undergraduate students. The following properties were studied: internal consistency in 4 sets of items (Cronbach α), test-retest reliability among closed-ended questions (κ statistics and intraclass correlation coefficient), and construct validity (associations with other validated instruments, such as the Alcohol Use Disorders Identification Test). For a section of questions showing low reliability, the answers to open questions and other in-depth interviews were carried out, and online surveys were conducted with another sample of undergraduate students to evaluate reliability after changes.Results:Eight students participated in the in-depth interviews, 177 responses from the online survey were included for the analysis of internal consistency, 115 for test-retest reliability, and 98 for construct validity. The 4 sets of items (sections) evaluated (“impact of alcohol consumption on academics,” “impact of microaggressions,” “witnessing microaggressions and alcohol intoxication,” and “bystanders’ interventions on alcohol intoxication”) presented good internal consistency (Cronbach α between 0.723 and 0.898). Most items showed moderate to substantial test-retest reliability; agreement was from 68.1% to 95.2%, and κ coefficients ranged from 0.214 to 0.8. For construct validity, correlations between the number of drinking days, the maximum number of drinks in a day and the Alcohol Use Disorders Identification Test score were moderate to high, r=0.630 (95% CI 0.533-0.719) and r=0.647 (95% CI 0.548-0.741), respectively. Due to low reliability, a section regarding “health impacts” has been redesigned, including 8 items for the personal consumption of alcohol and the consumption of others (Cronbach α 0.735 and 0.855, respectively; agreement between the first and the second time the questionnaire was administered were 83.4% and 99.1%, and most of the items with κ coefficient from 0.476 to 0.877).Conclusions:The revised version of the Color of Drinking questionnaire showed acceptable to adequate reliability and construct validity.